Study of Catalytic Activity of Silica Supported Schiff Base Complexes - Deshmukh, J.M.; Mahind, L.H.; Waghmode, S.A.; Dagade, S.P. (Asian Journal of Chemistry, 2017)
The catalytic activity of silica supported Schiff base metal complexes have been studied for the oxidation of benzyl alcohol, using hydrogen peroxide, which gave benzaldehyde as a major product. Silica supported Schiff base complexes gave better results compared to unsupported Schiff base complexes. Schiff base metal complexes such as Cr(VI), Mo(VI) and W(VI) have played significant role to enhance their conversion and selectivity. Among these Cr(VI) showed better conversion.